Impact of intravenous tranexamic acid on patients undergoing shoulder arthroplasty surgery. (June 2022) - Kissin, E; Al-Tawil, K; Tavakkolizadeh, A; Sinha, J; Colegate-Stone, T
Background: Shoulder arthroplasty surgery carries the risk of blood loss. The antifibrinolytic tranexamic acid (TXA) is effective in reducing blood loss in lower limb arthroplasty. The purpose of this study was to assess blood loss and associated complications following shoulder arthroplasty performed with and without TXA for both elective and trauma indications. Methods: A cohort study was performed to assess blood loss, transfusion requirements and post-operative venous thromboembolic events (VTE) following shoulder arthroplasty undertaken with and without the use of intravenous TXA. Results: The study consisted of 67 patients ( n = 36 with TXA; n = 31 without TXA). Type of arthroplasty included reverse-shoulder arthroplasty, total-shoulder arthroplasty and hemiarthroplasty. There was no significant difference between TXA and non-TXA groups regarding blood loss (TXA group haemoglobin drop 20.6 mg/dL; non-TXA group haemoglobin drop 20.5 mg/dL; p = 0.978). There was no significant difference in measured outcomes with or without TXA use for elective or trauma indications, nor regarding type of arthroplasty. Discussion: The use of intravenous TXA in shoulder arthroplasty was not associated with a significant reduction in blood loss or post-operative transfusion rates, nor did it impact on VTE. This result was not affected by the indication being elective or trauma nor the type of arthroplasty surgery performed.